Navigating Ostracism Behavior and Workplace Isolation in the IoT Era : A Mindfulness-Based Intervention Approach for Employee Well-Being - Vajpayee, Aparna; Kumar, Arun; Sanghani, Parag (Prabandhan: Indian Journal of Management, 2025)
Purpose : This study investigated the impact of the Internet of Things (IoT)-driven monitoring on employee ostracism and evaluated the effectiveness of a structured mindfulness program in mitigating exclusion and distress. Design/Methodology/Approach : A quasi-experimental design was employed with 40 employees (25–45 years old) from the technology, manufacturing, and finance industries. Participants underwent an eight-week mindfulness program (90 minutes/week, hybrid delivery) including psychoeducation, counseling, mindfulness practices, and social integration. The Five Facet Mindfulness Questionnaire (FFMQ) was used, and data were analyzed using SEM in AMOS. Findings : The intervention was successful in increasing mindfulness facets (observing, describing, and awareness), reducing ostracism by 30%, reducing stress by 40%, and increasing social connectedness by 35%. SEM verified that mindfulness facets mediated the reduction of ostracism and emotional distress, thereby increasing collaboration and empowerment. Practical Implications : The findings could be applied to HR intervention plans, leadership training, and workplace regulations to combat technostress and digital exclusion in Industry 5.0 workplaces. Originality/Value : This research distinguished digital ostracism from its offline counterpart and proposed mindfulness as a viable intervention to bolster employee wellness in Internet-of-Things work settings.